Determinants of Environmental Performance: The Role of Green Supply Chain Management in Linking Internal and External Factors : Study on SMEs in Central Papua - Agung Nugroho (Jurnal Simki Economic, 2026)
This study examines the determinants of environmental performance of micro, small, and medium enterprises (SMEs) in Central Papua by analyzing the roles of strategic orientation, internal environment management, and government regulation, with Green Supply Chain Management (GSCM) as a mediating variable. Using a quantitative explanatory approach, data were collected from 400 SME owners and managers through structured questionnaires. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that internal environment management and government regulation have significant positive effects on both GSCM and environmental performance. GSCM is also found to have a direct and significant influence on environmental performance. Furthermore, GSCM partially mediates the relationships between internal environment management and environmental performance, as well as between government regulation and environmental performance. In contrast, strategic orientation does not significantly affect GSCM, and GSCM does not mediate the relationship between strategic orientation and environmental performance, although strategic orientation has a direct effect on environmental performance. These findings suggest that strong internal environmental systems and effective regulatory pressure are critical drivers of GSCM adoption and environmental performance improvement among SMEs. The study highlights the importance of integrating internal capabilities and regulatory frameworks with green supply chain practices to enhance sustainable environmental performance.